Students' Problem-Solving Skills through the Modified Triangle Method with Contextual Teaching and Learning - Dina Amsari; Salmaini Safitri Syam; Fadila Suciana (S&Co Publishing, 2025)
This research was motivated by the low level of students' problem-solving ability in mathematics learning, especially based on real-world problems. The main cause is that students still have problems in understanding the meaning and finding the core of the given problem. The objectives of this study to determine the modified Triangle Method (TM) with Contextual Teaching and Learning (CTL) to improv students' ability in problem-solving and also its interaction with prior knowledge. This type of research is experimental design with a sample of 69 students grade VIII in West Sumatera, Indonesia. The data were obtained by giving the test, which was evaluated by t-test and two-way ANOVA. Based on the result test, obtained a t-value of 4.488 with the Sig.=0.000<0.05= α. It can be concluded that the modified of TM and CTL can improve students' problem-solving ability. Meanwhile, the interaction test obtained Sig.0.467>0.05=α. In other words, there is no interaction between CTL and students' prior knowledge of problem-solving skills. It means that TM and CTL can be used for students with high and low prior knowledge to improve students' problem-solving skills.